Diagnostic Value of Next‐Generation Sequencing in an Unusual Sphenoid Tumor. (7th May 2014) - Jamshidi, Farzad; Pleasance, Erin; Li, Yvonne; Shen, Yaoqing; Kasaian, Katayoon; Corbett, Richard; Eirew, Peter; Lum, Amy; Pandoh, Pawan; Zhao, Yongjun; Schein, Jacqueline E.; Moore, Richard A.; et al.
Abstract : Extraordinary advancements in sequencing technology have made what was once a decade‐long multi‐institutional endeavor into a methodology with the potential for practical use in a clinical setting. We therefore set out to examine the clinical value of next‐generation sequencing by enrolling patients with incurable or ambiguous tumors into the Personalized OncoGenomics initiative at the British Columbia Cancer Agency whereby whole genome and transcriptome analyses of tumor/normal tissue pairs are completed with the ultimate goal of directing therapeutics. First, we established that the sequencing, analysis, and communication with oncologists could be completed in less than 5 weeks. Second, we found that cancer diagnostics is an area that can greatly benefit from the comprehensiveness of a whole genome analysis. Here, we present a scenario in which a metastasized sphenoid mass, which was initially thought of as an undifferentiated squamous cell carcinoma, was rediagnosed as an SMARCB1 ‐negative rhabdoid tumor based on the newly acquired finding of homozygous SMARCB1 deletion. The new diagnosis led to a change in chemotherapy and a complete nodal response in the patient. This study also provides additional insight into the mutational landscape of an adult SMARCB1 ‐negative tumor that has not been explored at a whole genome and transcriptome level. Abstract : The authors report the case of a patient for whom whole genome sequencing was instrumental in assisting in the correct diagnosis of the tumor based on the finding of homozygous SMARCB1 loss. This resulted in a switch in chemotherapy protocol, leading to diminution of the distant metastases. They conclude that cancer diagnostics is an area that can greatly benefit from the comprehensiveness of a whole genome analysis.